Investigating the factors that affect the communication of death‐related bad news to people with intellectual disabilities by staff in residential and supported living services: An interview study. Issue 8 (7th April 2017) - Tuffrey‐Wijne, I.; Rose, T.
Abstract: Background: Most staff working in intellectual disability services will be confronted with people with intellectual disabilities who need support around death, dying and bereavement. Previous studies suggest that intellectual disability staff tend to protect clients from knowing about death and avoid communication about death. The aims of this study were to gain further insight into the individual, organisational and contextual factors that affect the communication of death‐related bad news to people with intellectual disabilities by intellectual disability staff and to develop guidelines for services to enable appropriate communication with clients about death and dying. Method: Semi‐structured interviews were held with 20 social care staff working in intellectual disability residential or supported living services in London, who had supported a client affected by death‐related bad news in the past 6 months. Results: Staff found supporting people with intellectual disabilities around death and dying extremely difficult and tended to avoid communication about death. The following factors had a particularly strong influence on staff practice around communicating death‐related bad news: fear and distress around death; life and work experience; and organisational culture. Staff attitudes to death communication had a stronger influence than their client's level of cognitive or communicative abilities. Managers were important role models. Conclusions: Service managers should ensure not only that all their staff receive training in death, loss and communication but also that staff are enabled to reflect on their practice, through emotional support, supervision and team discussions. Future work should focus on the development and testing of strategies to enable intellectual disability staff to support their clients in the areas of dying, death and bereavement.